2006
DOI: 10.1002/jsfa.2693
|View full text |Cite
|
Sign up to set email alerts
|

Water distribution in smoked salmon

Abstract: Low-field 1 H nuclear magnetic resonance (NMR) tranverse relaxations were measured on intact and minced muscle from raw and smoked salmon differing in size (small or large) and storage days after smoking (1, 11 and 20 days). Water distribution in the samples was calculated from the NMR signals by the use of multi-way data analysis. For intact and minced salmon samples, three water 'pools' with T 2 values of 38, 50 and 182 ms and of 33, 50 and 183 ms, respectively, were identified. For both intact and minced sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Before salting, there were two main populations centered at 20-100 ms (T 21 ) and 100-300 ms (T 22 ). These findings are in agreement with earlier studies of pork (4, 5, 7, 40) and fish (8, 10,17,18,20). The water populations changed within the range 20-300 (T 21 ) and 100-1000 (T 22 ) during salting, depending on both fish species and brine concentration.…”
Section: Low-field (Lf) 1 H Nmrsupporting
confidence: 93%
“…Before salting, there were two main populations centered at 20-100 ms (T 21 ) and 100-300 ms (T 22 ). These findings are in agreement with earlier studies of pork (4, 5, 7, 40) and fish (8, 10,17,18,20). The water populations changed within the range 20-300 (T 21 ) and 100-1000 (T 22 ) during salting, depending on both fish species and brine concentration.…”
Section: Low-field (Lf) 1 H Nmrsupporting
confidence: 93%
“…The observed changes in LHC may be related to changes seen in water distribution. The water pool data used in the PLSR model where those reported by Løje et al 31 They found that the water distribution in smoked salmon was affected by chill storage, as a decrease in the size of water pool II and a concurrent increase in the size of water pool I were seen during chill storage from day 1 to day 20 after smoking, with the greatest change occurring between days 1 and 11. In a study of thawed cod packed in a modified atmosphere, a similar change in water distribution was also observed during chill storage, where an increase in the size of water pool I at the expense of pool II was found to correspond to the denaturation of muscle protein and a simultaneous change in pH 33…”
Section: Resultsmentioning
confidence: 95%
“…The PLSR model was calculated for intact smoked salmon samples and the relationship between response variables ( X ) and design variables ( Y ) was explored. The water pool data used in the PLSR model were those reported by Løje et al 31 The Y matrix consisted of indicator variables (values either 0 or 1) for storage days (1, 11 or 20 days) and group of fish (farm 1 small, farm 2 small, farm 1 large or farm 2 large). All models were calculated by segmented cross‐validation with 10% of the samples, randomly selected, in each segment.…”
Section: Methodsmentioning
confidence: 99%
“…However, as a perishable food, particular preservation method is required for turbot. Freezing is a proper method of preserving food for a long time [3], which prevents microbial growth and reduces the enzyme activity, whereas frozen flesh inevitably suffers repeated freezing-thawing processes in circulation [4][5][6]. It is noteworthy that cellular damage is caused by the formation of ice within the tissue in freezing, and the result could be the serious fall in the quality of flesh [7].…”
Section: Introductionmentioning
confidence: 99%
“…LF-NMR measures the proton relaxation by spin-lattice relaxation time (T 1 ) and spin-spin relaxation time (T 2 ), which reflects water mobility and distribution of different compositions. The parameter of NMR is related to the parameters of flesh quality, such as color, shear force, and thiobarbituric acid-reactive substances (TBARS), which is useful in the evaluation of the quality of food [5,[11][12][13][14][15][16][17]. Magnetic resonance imaging (MRI), the other type of NMR technology, provides the information about the internal distributed status of water in food, which has been employed for food processing and analysis [18].…”
Section: Introductionmentioning
confidence: 99%